PENGARUH MARKETING COMMUNICATION, KUALITAS PRODUK, DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN SURAT KABAR HARIAN SUARA MERDEKA ( Studi pada PT. Suara Merdeka Press Semarang ) - Ghaisani, Meiditha Afidanti; Waloejo, Handoyo Djoko (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2018)
In the current era of globalization, demanding society to always follow the actual information and news. Newspaper is one type of mass media, which is able to present a lot of information and news updates. One of the newspaper printing companies in Central Java, is PT. Suara Merdeka Press. Even though the sales target of Suara Merdeka daily sales tends to be stable, the facts are still not reaching 100% target although the sales target is relatively realistic from year to year. This study aims to determine the effect of Miteting Communication, Product Quality and Brand Image on the Decision of Purchasing Suara Merdeka newspaper. This type of research is explanatory research, in which data collection techniques are used, namely questionnaires. The sample selected amounted to 100 people with accidental sampling and purposive sampling. The respondents are consumers who purchase a newspaper product Suara Merdeka. Data analysis used were validity test, reliability test, correlation coefficient, coefficient of determination, simple linear regression, multiple linear regression, and significance test (t and F test) with SPSS version 22.Based on the results of the study note that Marketing Communication variables contribute influence on Purchase Decision by 40.8%. Product Quality Variables contribute influence to the Purchase Decision of 40.2%. Variable Brand Image contributes influence to the Purchase Decision of 36.2%. While simultaneously Product Quality, Service Quality, and Brand Image contributed to the influence of the Purchasing Decision of 52.8%. That is, the better Maketing Communication, Product Quality, and Brand Image, the higher the decision to Purchase Suara Merdeka newspaper products.